Svetlova A. I. Polyfunctionality and polyaspectedness of communicative silence in the English belles–lettre discourse - Svetlova A. I. (Philological Treatises, 2020)
The article deals with communicative silence, its place in the English literary discourse. Communicative silence polymodality is defined by its diversity, surroundings, conditions and the ways of its presentation.